Fenomena Penggunaan Artificial Intelligence (AI) Dalam Pembelajaran: Analisis Proses Berpikir Siswa Di Era Digital Perspektif Teori Kognitif - Rizka Maulidatun Nadifah; Istanade Habibi Nasrullah; Ivo Sindia Nur Azizah (Journal of Humanities, Social Sciences, and Education, 2026)
This study aims to analyze students’ experiences in using Artificial Intelligence (AI) in the learning process based on the cognitive theories of Jean Piaget and Jerome Bruner. This research employed a qualitative phenomenological approach to explore students’ subjective experiences in utilizing AI as part of the knowledge construction process. The participants consisted of eight tenth-grade students selected through purposive sampling. Data were collected through in-depth interviews, classroom observations, documentation, and questionnaires. The data were analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. The findings revealed three main themes related to students’ experiences with AI: AI as digital scaffolding for understanding complex materials, AI as a facilitator of cognitive schema transformation through assimilation and accommodation processes, and the challenges of AI use toward students’ cognitive engagement and critical thinking. AI helped students simplify abstract concepts, visualize information, connect new knowledge with prior understanding, and correct misconceptions through immediate feedback. However, the findings also indicated that excessive dependence on AI-generated answers may reduce students’ deep cognitive processing, as some students tended to accept information without independent analysis and reflection. Therefore, teachers’ pedagogical guidance remains essential in directing AI use through reflective learning strategies, critical questioning, and AI literacy development. This study concludes that AI can serve as an effective learning mediator when integrated appropriately to enhance students’ critical thinking, independent learning, and knowledge construction processes in the digital era.